Fuzzy Controlled Architecture for Performance Tuning of Database Management System - pandey, Rajneesh kumar; singh, Yashwant kumar; Milan, Ram (IJRDO -Journal of Computer Science Engineering, 2017)
Database Management Systems deliver higher performanceonly when they are properly tuned. Database tuning iscomplicated due to the fact that several conflicting tuningparameters have to be adjusted simultaneously for a variety ofworkload types and the highly unpredictable traffic patterns.The Database Administrator(DBA) has to be an expert andusing his experience and expertise must judiciously decide theextent of tuning of the most important tuning factors so as toensure the required level of performance in terms of responsetime and throughput. The process of tuning being complexand to keep the cost of ownership low, it is desirable to buildself tuning database systems. In this paper, a new tuningarchitecture based on fuzzy logic is presented, where in, thecontrol action is expressed in linguistic terms. In this systemthe key performance indicators are fuzzified, appropriatefuzzy rules are employed to estimate the extent of tuningrequired for a few important tuning parameters. Afterdefuzzification, a control action is initiated to scale up thesystem performance. The experimental results obtained fordifferent workload types and the user load, indicate that it ispossible to significantly improve the query response timeusing this technique.